Trend in prevalence of coronary artery disease and risk factors over two decades in rural Punjab. Issue 2 (14th September 2017) - Goyal, Abhishek; Kahlon, Praneet; Jain, Dinesh; Soni, R K; Gulati, Rohit; Chhabra, Shibba Takkar; Aslam, Naved; Mohan, Bishav; Anand, Inder S; Patel, Vikram; Wander, Gurpreet Singh
Abstract : Objectives: The burden of coronary artery disease (CAD) has increased in the last three decades in low-income and middle-income countries including India. CAD is responsible for 20% deaths in India. The burden of CAD has increased due to a higher prevalence of risk factors related to the changing lifestyle. We studied the change in prevalence of CAD and risk factors over 20 years in a rural area. Methods: A rural population of adults over the age of 30 years from three villages of Punjab was surveyed for the prevalence of CAD and its risk factors in 1994 and 2014 using similar research methodology. CAD was diagnosed by Epstein and clinical criteria. Blood pressure, anthropometry, ECG and biochemical analysis were carried out. The findings of two surveys were compared with a look at the change in the prevalence of CAD and its risk factors over 20 years. Results: The overall age standardised prevalence of CAD increased from 2.79% in 1994 to 4.06% (p<0.05) in 2014. There was a significant increase in the prevalence of several risk factors including sedentary lifestyle (8.2% vs 41.3%, p<0.001), hypertension (14.5% vs 26.5%, p<0.001), diabetes (4.7% vs 9.7%, p<0.001), obesity (16.6% vs 35.4, p<0.001) and hypercholesterolaemia (7% vs 9.6%, p 0.011). In contrast, cigarette smoking (8.9% vs 3%, p<0.001) and use of desi ghee (51.4% vs 28.5%, p<0.001) decreased. Conclusions: In a rural population of Punjab, the prevalence of several CAD risk factors like sedentary lifestyle, hypertension, diabetes, obesity and hypercholesterolaemia increased over 20 years. These changes in risk factors were associated with a modest increase in prevalence of CAD.